(untitled) (Research, Society and Development, 2020)
This study aims to find answers to the suitability of the conditions for death in the dismissal of constitutional judges. The inclusion of death requirements in Law no. 7-2020 violates the true essence of death. Passing away cannot be regulated and it is better if the sound of the article is changed, which initially dismissed a constitutional judge with respect from becoming a constitutional judge to stop immediately if ...and death must be removed unless there is a better condition for this to happen.